High Levels of CD244 Rather Than CD160 Associate With CD8+ T-Cell Aging - Wang, Xinyue; Wang, Di; Du, Juan; Wei, Yuqing; Song, Rui; Wang, Beibei; Qiu, Shuang; Li, Bei; Zhang, Leidan; Zeng, Yongqin; Zhao, Hongxin; Kong, Yaxian (Frontiers in Immunology, 2022)
Aging leads to functional dysregulation of the immune system, especially T cell defects. Previous studies have shown that the accumulation of co-inhibitory molecules plays an essential role in both T cell exhaustion and aging. In the present study, we showed that CD244 and CD160 were both up-regulated on CD8+ T cells of elderly individuals. CD244+CD160- CD8+ T cells displayed the increased activity of β-GAL, higher production of cytokines, and severe metabolic disorders, which were characteristics of immune aging. Notably, the functional dysregulation associated with aging was reversed by blocking CD244 instead of CD160. Meanwhile, CD244+CD160+ CD8+ T cells exhibited features of exhaustion, including lower levels of cytokine, impaired proliferation, and intrinsic transcriptional regulation, compared to CD244+CD160- population. Collectively, our findings demonstrated that CD244 rather than CD160 acts as a prominent regulator involved in T cell aging, providing a solid therapeutic target to improve disorders and comorbidities correlated to immune system aging.